Desain Pembelajaran IPA Terintegrasi Mitigasi Bencana Tanah Longsor melalui Pendekatan Stem Pada Konsep Gerak Di SMP - Noni, Noni Noviana; Rita Sartika; Widia Gusti; Andika Pradipta; Henny Johan (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
Bengkulu Province is one of the areas in Indonesia that often experiences landslides, especially during the rainy season. Therefore it is necessary to have landslide disaster mitigation education for students. The purpose of this study was to design integrated natural science learning for landslide relief. The method used is qualitative with a descriptive approach. Data collection through teacher interviews, syllabus analysis, and literature study. Then the data obtained were analyzed to obtain a learning design. The results of this study are science learning designs that are integrated with landslide disaster mitigation. The concept of IPA that can be inserted is motion, namely Newton's law, where landslides occur due to movement in the ground. The learning process can be carried out using the STEM approach with the PJBL (Project Based Learning) model. So that this learning design will be contextual because it relates to everyday life. This learning design will later make working in groups in designing simple student technology as a response to landslide disasters. It is hoped that after learning students will more easily understand the concept of science because it is integrated with landslide disasters which are close to their lives and can apply it in everyday life.